Pertanian Perkotaan, Solusi Inovatif untuk Ketahanan Pangan di Tengah Kota - Marni Putri Gea; Restu Jaya Zendrato; Septian Oktani Telaumbanua; Ayler Beniah Ndraha (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Rapid urbanization has led to an increased demand for food in urban areas. At the same time, land limitations and dependence on external supplies pose significant challenges to food security. Urban agriculture is an innovative solution for producing local food using limited land and modern agricultural techniques such as hydroponics, aquaponics, vertical farming, and rooftop gardens. This approach allows urban agriculture to be more resource-efficient, reduces distribution costs, and minimizes its environmental impact by lowering its carbon footprint. In addition to environmental benefits, urban agriculture also brings social and economic benefits by raising awareness of food sustainability, creating new business opportunities, and enhancing food independence in urban communities. This research uses a literature review method to examine various articles discussing the development, obstacles, and implementation of urban agriculture in different countries. The results show that urban agriculture makes an important contribution to improving food security while also providing a sustainable alternative for the global food system. Therefore, promoting the growth of urban agriculture from the perspective of sustainable food security requires support from government institutions, the private sector, and local communities.